Pengaruh Omnichannel Integration Quality Terhadap Niat Pembelian Dimediasi Kepercayaan Konsumen Di Surakarta - Sidiq Permono Nugroho; Nina Sri Lestari; Edi Priyono; Triyanto Triyanto (Universitas Muhammadiyah Surakarta, 2023)
This research is related to Omnichannel integration quality and purchase intention and consumer trust. This study aims to determine the influence of Omnichannel integration quality on purchase intentions mediated by coffee consumer confidence in Surakarta. This research uses causal quantitative research. This study's population consisted of all coffee users at Cafe Surakarta, with an infinite number of participants and a total sample of 100 respondents. The sampling approach employs unintentional sampling. According to the study's findings, the layout of service channels has a considerable beneficial impact on purchase intentions. Consumer confidence is significantly boosted via service channels. The configuration of service channels has a considerable beneficial impact on purchase intentions, which are mediated through customer trust. Integrated contact has no discernible detrimental impact on purchasing intent. Consumer trust is affected through integrated interactions. Purchase intentions are significantly influenced by integrated interactions, which are mediated by customer trust.